Restoration and Rebuilding of Forestry Ecological System in Heilongjiang Province - 聂绍荃 张艳华 朱虹 (Journal of forestry research, 1997)
The study on restoration and rebuilding of forestry ecological system was conducted on Xianfeng Porestry Farm (N45° 03′, E 129°45′), in Yilan county. Heilongjiang province. One thousand hectare sample land was established. The research summarized the comprehensive technique measures: to managed virgin forests perfectly: to promote forest reforestation by artificial treatment; to restore the secondary forest with patch pattern; and to restore and foster felling land on artificial forest by means of natural pattern or close hillside to facilitate afforestation. The results showed that forest ecosystem function and quality were restored and rebuilt during ten years by utilization of these technique measures.